Microwell Array Based Opto‐Electrochemical Detections Revealing Co‐Adaptation of Rheological Properties and Oxygen Metabolism in Budding Yeast. Issue 7 (9th May 2021) - Vajrala, Venkata Suresh; Alric, Baptiste; Laborde, Adrian; Colin, Camille; Suraniti, Emmanuel; Temple‐Boyer, Pierre; Arbault, Stephane; Delarue, Morgan; Launay, Jérôme
Abstract: Microdevices composed of microwell arrays integrating nanoelectrodes (OptoElecWell) are developed to achieve dual high‐resolution optical and electrochemical detections on single Saccharomyces cerevisiae yeast cells. Each array consists of 1.6 × 10 5 microwells measuring 8 µm in diameter and 5 µm height, with a platinum nanoring electrode for in situ electrochemistry, all integrated on a transparent thin wafer for further high‐resolution live‐cell imaging. After optimizing the filling rate, 32% of cells are effectively trapped within microwells. This allows to analyse S. cerevisiae metabolism associated with basal respiration while simultaneously measuring optically other cellular parameters. In this study, the impact of glucose concentration on respiration and intracellular rheology is focused. It is found that while the oxygen uptake rate decreases with increasing glucose concentration, diffusion of tracer nanoparticles increases. The OptoElecWell‐based respiration methodology provides similar results compared to the commercial gold‐standard Seahorse XF analyzer, while using 20 times fewer biological samples, paving the way to achieve single cell metabolomics. In addition, it facilitates an optical route to monitor the contents within single cells. The proposed device, in combination with the dual detection analysis, opens up new avenues for measuring cellular metabolism, and relating it to cellular physiological indicators at single cell level. Abstract : A novel microwell array device that can blend both electrochemical and high‐resolution optical sensing technologies is presented. Dual detection of cellular oxygen consumption and single particle diffusion measurements within yeasts is demonstrated. Proof‐of‐concept study shows the co‐adaptation of cellular oxidative phosphorylation and rheological properties under substrate control.